How to evaluate an advance care planning policy – strategies for each stage of implementation. Issue 2 (1st June 2012) - Wityk Martin, TL; Berg, B; Simon, J
Abstract : In 2008, the "Advance Care Planning: Goals of Care Designation (Adult)" policy (ACP:GCD) was systematically implemented throughout the Calgary Zone of Alberta Health Services. A comprehensive evaluation plan was imbedded pre and post implementation across all health sectors. Key indicators were identified to measure policy outcomes. A diverse and flexible evaluation model was developed for differing stages of implementation. Evaluation successes and challenges will be outlined. The outcomes achieved demonstrate the successes of a comprehensive ACP policy framework. Our evaluation approach was critical to ensuring full policy integration. A large scale comprehensive chart audit was conducted across all sectors at baseline, 6 and 18 months post implementation; additional charts were reviewed as needed (total of 18669 charts). Key outcomes relating to policy implementation, transfer of information, and end of life care preferences being followed were achieved in all sectors. At 18 months, 4 out of 5 sectors had GCDs on at least 93% of their charts. GCDs transferred from acute care to facility living 84% of the time. 97% of GCDs were followed at end of life. Outcome data informed strategies for ongoing integration of the policy, areas for continued quality improvement and gaining and sustaining organisational support. Three years post implementation, a different approach to evaluation is required. Although data demonstrates increasing adherence to policy principles, areas for continued improvement were also identified. We will present targeted quality improvement activities being used to address gaps and barriers.